Design and Synthesis of Naphthol Derivative Using Three Components System and Its Relation with Physicochemical Parameters log P and p - Figueroa-Valverde, L.; Diaz-Cedillo , F.; García-Cervera, E.; Pool Gómez, E.; Cordova-Vazquez, Johany (Asian Journal of Chemistry, 2013)
A naphthol derivative was synthesized using the three-component system (b-naphthol, benzaldehyde and N-(2-aminoethyl)-4-hydroxybenzamide) and characterized by spectral analyses. In order to characterize the structural and chemical requirements of naphthol derivative, some parameters such as log P and p were evaluated. The results showed an increase in the values of log P and p for the compound 4 in comparison with 1, 2 and 3. These data indicate a high degree of lipophilicity and steric impediment for compound 4 in comparison with 1, 2 and 3.